2013
DOI: 10.1128/aac.02437-12
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Dysfunction Is the Focus of Quaternary Ammonium Surfactant Toxicity to Mammalian Epithelial Cells

Abstract: dSurfactants have long been known to have microbicidal action and have been extensively used as antiseptics and disinfectants for a variety of general hygiene and clinical purposes. Among surfactants, quaternary ammonium compounds (QAC) are known to be the most useful antiseptics and disinfectants. However, our previous toxicological studies showed that QAC are also the most toxic surfactants for mammalian cells. An understanding of the mechanisms that underlie QAC toxicity is a crucial first step in their rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
52
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(52 citation statements)
references
References 36 publications
0
52
0
Order By: Relevance
“…Furthermore, there are studies that indicated the potential genotoxic effects of QACs to exposed eukaryotic cells at concentrations commonly found in wastewaters and employed in commercially available nasal preparations (Deutschle et al, 2006;Ferk et al, 2007). An in vitro study conducted by Inacio and coworkers has shown that QACs cause mitochondrial dysfunction in the mammalian epithelial cell (Inacio et al, 2013). Melin et al (2014) also reported that exposure of mice to QAC disinfectant significantly damaged its reproduction health.…”
Section: Toxicity and Risk Assessments Of Qacsmentioning
confidence: 97%
“…Furthermore, there are studies that indicated the potential genotoxic effects of QACs to exposed eukaryotic cells at concentrations commonly found in wastewaters and employed in commercially available nasal preparations (Deutschle et al, 2006;Ferk et al, 2007). An in vitro study conducted by Inacio and coworkers has shown that QACs cause mitochondrial dysfunction in the mammalian epithelial cell (Inacio et al, 2013). Melin et al (2014) also reported that exposure of mice to QAC disinfectant significantly damaged its reproduction health.…”
Section: Toxicity and Risk Assessments Of Qacsmentioning
confidence: 97%
“…Mitochondria act as sensors and amplifiers in determining the execution of cell death or apoptosis through regulation of cellular energy metabolism (mitochondrial respiration and oxidative phosphorylation) [377]. Mitochondrial dysfunction and perturbation of cellular energetic mechanisms are involved in QAC-induced toxicity [367,[378][379][380]. At very low concentrations, QACs inhibit mitochondrial respiration and oxidative phosphorylation.…”
Section: Toxicological Aspects Of Qacsmentioning
confidence: 99%
“…With regard to a model of cell membranes as a fluid‐like bilayer arrangement of phospholipids, the cytotoxic effect of QAS is generally attributed to their penetration into phospholipids membrane and formation of membrane lipid/protein‐QAS mixed micelles resulting in disruption of cell membrane integrity and membrane ruptures . However, as the cytotoxicity of QAS was observed also at low doses where the cell lysis was not observed , the toxic effects can occur also as a result of membrane potential changes due to blocking of potassium channels , mitochondrial dysfunction or cell cycle arrest .…”
Section: Introductionmentioning
confidence: 99%